Post-traumatic Growth in the First COVID Outbreak in Hong Kong - Lau, Bobo Hi Po; Chan, Cecilia Lai Wan; Ng, Siu Man (Frontiers in Psychology, 2021)
Post-traumatic growth (PTG) emerges from highly stressful situations. The COVID pandemic may qualify as one. This study investigated the PTG among Hong Kong citizens during the first outbreak in spring 2020, shortly after a large-scale social movement subsided. A longitudinal online survey was launched during the peak (Time 1) and the palliation (Time 2) of the outbreak. Among the 327 participants who completed both waves, 28.4% exhibited probable post-traumatic stress disorder at Time 1, while 18.0% reported significant PTG in at least one domain at Time 2. The interaction between sense of coherence and post-traumatic stress mediated the relationship between Time 1 perceived outbreak severity and Time 2 PTG, such that PTG was more likely among participants with higher post-traumatic stress and sense of coherence. PTG was also associated with a weaker contingency between Time 1 and Time 2 perceived outbreak severity. Echoing the transformational model, our findings show that both experienced stress and coping resources are essential for PTG to emerge. We also demonstrated how PTG may lead to more flexible risk perceptions according to the development of the outbreak.